Use of non-psychoactive residual biomass from Cannabis sativa L. for obtaining phenolic rich-extracts with antioxidant capacity (2021)
The present research aims to give an added value to the chain production of Cannabis sativa L plant, taking advantage of the non-psychoactive residual biomass (stems and leaves). Total phenolic content (TPC) and total antioxidant capacity (TAC) were analysed. A factorial design 23 was carried out using extraction time (T), Particle size (PS), and solid-solvent ratio (SS) as factors. The extractions were made with ethanol at 96% as solvent. The maximum concentration of TPC found was 1264.61 mg GA/g DW at 6:250 g/mL, 8 h, and 109.28 µm for SS, T and PS, respectively. Similarly, the maximum TAC obtained was 0.467 mM Trolox equivalent, at 8 h, 6:250 g/mL and 109.28 µm for T, SS and PS, respectively. Additionally, the presence of oil was found in some samples of cannabis extracts for which FITR was performed, obtaining the presence of C-OH bonds associated with alcohols, phenols and possible cannabinoids.